The Effectiveness of M-Kia Applications on Mothers Toddlers on Early Detection and Prevention of Pneumonia in Demak Regency - Kurniawan, Chandra; Sutiningsih, Dwi; Martini, Martini (Journal of World Science, 2022)
Introduction: Factors that cause high pneumonia cases, including age less than two years, population density, winter, antibiotic resistance, daycare attendance, exposure to cigarette smoke, nutritional status, and the influence of comorbidities. Methods: The research method used in this study is a quantitative study with a cross-sectional approach aimed at seeing the relationship between the effectiveness of early detection of pneumonia using an application system. The results of this study are used to develop prevention and control strategies for pneumonia that reach all levels of society, especially marginal groups and provide recommendations related to child pneumonia advocacy. Results: The results of this study are 1) People in Demak who have almost 50 percent of toddlers say the M-KIA application cannot operate or open the M-KIA application; 2) There are still many people in Demak who have toddlers who say the M-KIA application does not understand and is not clear in meeting the needs for their toddlers. Most mothers of children under five in Demak with the M-KIA application are able to detect pneumonia early; 3) The M-KIA application is less effective because parents of toddlers in Demak have not all felt the function of the M-KIA application in meeting the health needs of toddlers, especially for early detection of pneumonia. Conclusion: The obstacle faced by the community in DEmak is the lack of knowledge of using the M-KIA application so that only some understand so that they feel the use of the M-KIA application to detect pneumonia in toddlers early